Corporate governance structures and carbon disclosure quality: a dynamic panel analysis with environmental performance moderation - Reddivari, Archana; Paramita, Melinda W.; Safira, Safira; Payamta, Payamta (Proceeding International Conference on Accounting and Finance, 2026)
Climate change has elevated the importance of transparent carbon disclosure as firms face increasing scrutiny from regulators, investors, and global stakeholders. In emerging economies, however, disclosure practices remain uneven due to voluntary reporting regimes and varying governance capacities. This study investigates how corporate governance structures, specifically board size and sustainability committee capacity influence carbon disclosure quality, and examines whether this relationship is strengthened by firms’ environmental performance. Using a balanced panel of 185 non‑financial manufacturing firms listed on the Indonesia Stock Exchange from 2018 to 2024, the analysis employs two‑step System Generalized Method of Moments (System GMM) to address endogeneity, unobserved heterogeneity, and the dynamic nature of disclosure behavior. Carbon disclosure quality is measured through a weighted index derived from GRI 305 and the Greenhouse Gas Protocol, while environmental performance is captured using Indonesia’s PROPER rating system. The results show that carbon disclosure is strongly persistent across years, and both board size and sustainability committee capacity significantly enhance disclosure depth. Environmental performance not only improves reporting quality directly but also strengthens the effect of sustainability committee capacity, indicating a complementary relationship between internal governance oversight and verified environmental achievement. These findings contribute to climate‑governance literature by integrating governance structures, external performance validation, and the dynamic progression of carbon reporting. They also offer practical insights for firms and regulators seeking to improve climate‑related transparency.